Komunikasi organisasi dan penilaian kinerja sebagai akar masalah organisasi - M. Ghazali Bagus Ani Putra (INNER: Journal of Psychological Research, 2022)
Abstract The various kinds of organizational problems faced cannot necessarily be found at the root of the problem. So that the handling of organizational problems has not been effective because they have not found the root of the problem. Therefore, the purpose of this study was to analyze the root causes of organizational problems in private hospitals in Yogyakarta. The approach used in this research is a qualitative approach with an instrumental case study type. The research participants were 15 people who were given interview data collection methods and focus group discussions. To find the root of the problem, this research uses stream analysis. The results of this study indicate that the root of the problem in the setting of this research is one-way organizational communication and subjective performance appraisal. While the recommendation for the root of this problem is third party intervention for organizational communication problems and the preparation of a data/evidence-based performance appraisal system. Keywords: organizational communication, performance appraisal